Adsorbed Natural Gas Storage for Onboard Applications. (11th February 2021) - Wu, Zhongjie; Wee, Vanessa; Ma, Xinbin; Zhao, Dan
Abstract: Given its abundance and clean combustion, natural gas (NG) is one of the leading sources of energy to meet present demands. However, the storage and transportation of NG remain challenging. Besides the commonly used NG storage methods such as compression and liquefaction, adsorbed NG is an attractive alternative. Here, the requirements for vehicles to be powered by adsorbed natural gas (ANG) are examined. Despite top‐performing adsorbents and present‐day engineering solutions, there remain obstacles that prevent vehicles fueled by ANG from becoming commonplace. Herein, these challenges are highlighted to inspire engineering solutions for onboard ANG systems. Abstract : While natural gas may meet today's energy demands, its storage and transportation remain challenging. Nonetheless, adsorbed natural gas (ANG) is promising for vehicular applications. By examining top‐performing adsorbents and modern engineering solutions, this review discusses the requirements of ANG‐fueled vehicles and hopes to inspire engineering solutions for future onboard ANG systems.